1972
DOI: 10.1002/app.1972.070160409
|View full text |Cite
|
Sign up to set email alerts
|

Thermally stable polyimides from solutions of monomeric reactants

Abstract: A method to prepare thermally stable resin fiber‐reinforced composites using solutions of appropriate monomers is described. Solutions containing a dimethyl ester of an aryl tetracarboxylic acid, the monomethyl ester of 5‐norbornene‐2,3‐dicarboxylic acid and an aryl diamine were used to impregnate graphite fibers. Composites fabricated from these prepregs exhibited excellent thermo‐oxidative stability and retention of mechanical properties at 600°F. These results compare favorably with those obtained from comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
210
0

Year Published

1976
1976
2011
2011

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 364 publications
(214 citation statements)
references
References 3 publications
3
210
0
Order By: Relevance
“…These additives appear to increase the rate of nadimide polymerization at lower . 1 temperatures. The purpose of this report is to demonstrate the feasibility of using nitrophenylnadimides and other nitro substituted compounds to lower the cure temperature of PHR-15 composites and to identify the processing parameters and resultant composite performance characteristics.…”
Section: )mentioning
confidence: 98%
“…These additives appear to increase the rate of nadimide polymerization at lower . 1 temperatures. The purpose of this report is to demonstrate the feasibility of using nitrophenylnadimides and other nitro substituted compounds to lower the cure temperature of PHR-15 composites and to identify the processing parameters and resultant composite performance characteristics.…”
Section: )mentioning
confidence: 98%
“…The low bending strength could be improved by further studying the mechanical properties at high temperatures and by optimizing the preparation method of FRP. An FRP (Yokohama Rubber Co., Ltd.), which was prepared using polyimide resin (PMR-15); developed by NASA-Lewis Research Center [32] and a silicon carbide compact is shown on the graph below 300°C. Dynamic viscoelasticity and creep properties of MSP composite were determined and compared with those of a polyimide composite [30].…”
Section: (1) Composite Materialsmentioning
confidence: 99%
“…A common practice is to create a neat resin sample -one with no reinforcing material added -to allow for chemical and mechanical testing to be performed on the cured resin. For high-temperature resins, such as PMR-15 5 and its https://ntrs.nasa.gov/search.jsp?R=20070022453 2019-04-28T05:41:58+00:00Z descendents, production of the resin sample requires the application of high temperatures (up to 650 °F) and substantial pressure (several hundreds pounds per square inch) using a specified time-temperature-pressure profile. This requires the resin to be processed in a heated compression tool made of hardened tool steel.…”
Section: Introductionmentioning
confidence: 99%